1998
DOI: 10.1136/jech.52.9.558
|View full text |Cite
|
Sign up to set email alerts
|

Generational continuity and change in British Asian health and health behaviour

Abstract: Objectives-To trace patterns of health and health behaviour in those with ancestry in the Indian subcontinent (British Asians) compared with the general population of their age (1) in the younger generation age 14-15 mainly born in the UK and (2) in the older mainly migrant generation. Design-Cross sectional random sample surveys of two age groups in Glasgow. (J Epidemiol Community Health 1998;52:558-563) The health behaviour of British Asians (those with ancestry in the Indian subcontinent) is generally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“… [ 24 ] Pollard et al 2008 Cross sectional British Pakistani (60) European (25) Female 20 to 40 North East England Self-report, validated questionnaire -International Physical Activity Questionnaire [ 25 ] Pollard et al 2012 Cross sectional British Pakistani (67) White British (70) Female 9 to 11 North East England Accelerometer worn for 2 school days [ 26 ]Pomerleau et al 1999 Cross sectional South Asian (291) European (559), Afro-Caribbean (303) Female 40 to 69 London Self-report questionnaire [ 27 ] Riste et al 2001 Cross sectional Pakistani (132) European (471), African-Caribbean (316) Male and Female 35 to 79 Manchester Self-report validated questionnaire [ 28 ] Smith et al 2012 Cross sectional Indian, Pakistani, Bangladeshi White Male and Female 16 to 55 England Self-report questionnaire based on Allied Dunbar National Fitness Survey [ 29 ] Williams et al 1994 Cross sectional South Asian (173) General population (344) Male and Female 30 to 40 Glasgow Self-report questionnaire. [ 30 ] Williams et al 1998 Cross sectional British Asian (334) Other origin (490) Male and Female 14 to 15 in South Asians Age 35 in General population Glasgow Self-report questionnaire. [ 35 ] Williams et al 2010 Cross sectional South Asian Sikhs (571), Muslims (179), Hindus (315) Whites (818) Ma...…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… [ 24 ] Pollard et al 2008 Cross sectional British Pakistani (60) European (25) Female 20 to 40 North East England Self-report, validated questionnaire -International Physical Activity Questionnaire [ 25 ] Pollard et al 2012 Cross sectional British Pakistani (67) White British (70) Female 9 to 11 North East England Accelerometer worn for 2 school days [ 26 ]Pomerleau et al 1999 Cross sectional South Asian (291) European (559), Afro-Caribbean (303) Female 40 to 69 London Self-report questionnaire [ 27 ] Riste et al 2001 Cross sectional Pakistani (132) European (471), African-Caribbean (316) Male and Female 35 to 79 Manchester Self-report validated questionnaire [ 28 ] Smith et al 2012 Cross sectional Indian, Pakistani, Bangladeshi White Male and Female 16 to 55 England Self-report questionnaire based on Allied Dunbar National Fitness Survey [ 29 ] Williams et al 1994 Cross sectional South Asian (173) General population (344) Male and Female 30 to 40 Glasgow Self-report questionnaire. [ 30 ] Williams et al 1998 Cross sectional British Asian (334) Other origin (490) Male and Female 14 to 15 in South Asians Age 35 in General population Glasgow Self-report questionnaire. [ 35 ] Williams et al 2010 Cross sectional South Asian Sikhs (571), Muslims (179), Hindus (315) Whites (818) Ma...…”
Section: Methodsmentioning
confidence: 99%
“…Of the papers reporting on children, only one reported a power calculation for the sample size [ 30 ]. The other 11 papers provided no justification for their sample size; the majority only reported the number of people they had recruited, implying that their aim was to recruit as many children as possible into their studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Low levels of physical activity have been reported in adults and children of South Asian origin living in the UK, Canada and the US [1-8] and are thought to contribute to the high risk of type 2 diabetes and cardiovascular disease in this group [9-11]. Activity levels are particularly low in people with origins in Bangladesh or Pakistan, and in women and girls [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The 2004 Health Survey for England data reported lower levels of physical activity in South Asian groups compared with the general UK population and other ethnic minority groups (77), and other studies showed similar results in migrant and urban South Asians (6,15,82,83,84,85,86,87). This low level of physical activity is already present in children and adolescents (77,85,88,89,90,91).…”
Section: Diet and Exercisementioning
confidence: 85%